Innovation activities, sources of innovation and R&D cooperation: evidence from firms in Hong Kong and Guangdong Province, China. (1st January 2012) - Sharif, Naubahar; Baark, Erik; Lau, Antonio K.W.
In a globalised and knowledge-based economy, companies must innovate continuously. Recent studies suggest that companies create multiple types of innovation and should expand the boundaries of their knowledge-production processes to cooperate with external organisations for innovation. Extant empirical studies of relationships between internal and external innovation activities, R&D cooperation, and types of innovation in developed countries have yielded mixed results. As a prominent Asian newly industrialising economy (NIE), Hong Kong's innovation and technology management has rarely been studied. This study explores the innovation activities and performance of Hong Kong companies with operations in Guangdong. Using a survey – based on the community innovation survey 4 (CIS4) – of 492 companies, we have found that intramural and extramural R&D, acquisition of machinery, and R&D cooperation are important for product, process, organisational, or marketing innovation. A notable result is that market-related efforts play a key role in most innovation undertaken by firms under study.